The dark matter bispectrum from effective viscosity and one-particle irreducible vertices - Flörchinger, Stefan; Garny, Mathias; Katsis, Aris; Tetradis, Nikolaos; Wiedemann, Urs Achim (Journal of cosmology and astroparticle physics, 2019)
Dark matter evolution during the process of cosmological structure formation can be described in terms of a one-particle irreducible effective action at a characteristic scale km and a loop expansion below this scale, based on the effective propagators and vertices. We calculate the form of the effective vertices and compute the bispectrum of density perturbations within a one-loop approximation. We find that the effective vertices play a subdominant role as compared to the effective viscosity and sound velocity that modify the (inverse) propagators. For the bispectrum we reproduce the results of standard perturbation theory in the range where it is applicable, and find a slightly improved agreement with N-body simulations at larger wavenumbers.